2021
DOI: 10.1155/2021/5515759
|View full text |Cite
|
Sign up to set email alerts
|

Controlling an Anatomical Robot Hand Using the Brain-Computer Interface Based on Motor Imagery

Abstract: More than one billion people face disabilities worldwide, according to the World Health Organization (WHO). In Sri Lanka, there are thousands of people suffering from a variety of disabilities, especially hand disabilities, due to the civil war in the country. The Ministry of Health of Sri Lanka reports that by 2025, the number of people with disabilities in Sri Lanka will grow by 24.2%. In the field of robotics, new technologies for handicapped people are now being built to make their lives simple and effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…They employ the EEGNet, a convolutional neural network, for feature extraction and signal classification across five motorimagery hand tasks performed by users. In [21], 3-finger anatomical robot hand model is developed for handicapped people. Eight channel motor imagery EEG data from primary motor cortex is used to control (flexion and extension) the robot hand.…”
Section: Introductionmentioning
confidence: 99%
“…They employ the EEGNet, a convolutional neural network, for feature extraction and signal classification across five motorimagery hand tasks performed by users. In [21], 3-finger anatomical robot hand model is developed for handicapped people. Eight channel motor imagery EEG data from primary motor cortex is used to control (flexion and extension) the robot hand.…”
Section: Introductionmentioning
confidence: 99%
“…These years have witnessed thriving progress in the field of BCI. Motor imagery (MI) is one of the common paradigms in BCI research (Kaiser et al, 2011 ), which is accomplished by imagining performing the given task (Jeannerod, 1995 ), such as grabbing (Herath and Mel, 2021 ), lifting (Kasemsumran and Boonchieng, 2019 ), and so on. MI-BCIs are widely used to aid patients with motor function impairments caused by stroke (Ang et al, 2010 ), amyotrophic lateral sclerosis (Lulé et al, 2007 ), spinal cord injury (Cramer et al, 2007 ), and so on, either for daily-life assistance or rehabilitative training.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of cognitive neuroscience (Seitamaa-Hakkarainen et al, 2016 ; Chrysikou and Gero, 2020 ; Slagter and Bouwer, 2021 ), more and more scholars are considering the use of cognitive neural techniques for evaluating human-computer interaction performance. One of these, the Electroencephalogram (EEG), has proven to be a reliable indicator of spontaneous brain activity (Gevins et al, 1997 ; Stikic et al, 2011 ; Herath and de Mel, 2021 ). In Chen et al ( 2017 ), one electroencephalographic (EEG) method was proposed based on primary band power spectral density (PSD) to assess brain load tasks, and indicated that the channel in the left frontoparietal lobe (Fp1) had the highest correlation with brain load levels; In Kumar and Kumar ( 2016 ), the authors demonstrated that the average power in each band can be used for the characterization of cognitive load; In Ismail and Karwowski ( 2020 ), the authors summarized the research on EEG in the cognitive domain and indicated that the amplitude of some ERP components (e.g., P3, P2, N1, N2) decreased with increasing workload.…”
Section: Introductionmentioning
confidence: 99%